Study About the Knowledge and Attitudes of the Portuguese Population - Martinho, Célia (2013)
The association between dietary fiber, health benefits and healthy food has been studied in recent years. The food industry, to accompany the strong interest shown by consumers, has placed at their disposal new products, rich in dietary fiber. This work intended to make a statistical analysis of the knowledge of the Portuguese population about fibres, and for that a survey was conducted of a sample of 182 individuals. Some topics covered included consumption habits, knowledge about fibres, means of dissemination and information, food labelling or the relationship between fibres and health, among others. The most relevant results indicate that only 13% of respondents eat two meals a day with vegetables and/or salads and 9% eat at least 3 pieces of fruit. Whole grains are never consumed by only 41% and 18% do so at least once a week. Around 35% of respondents know about the origin of fibres whereas 70% say there is a greater amount of fibre in legumes, fruit with skin and whole foods. The consultation of food labels is of interest to 80% of respondents, although the fibre content is not of interest for 43% of respondents. The vast majority (90%) of respondents have the notion that fibre intake contrib- utes to the prevention and treatment of diseases. With this work it was concluded that the individuals in the survey reveal an insufficient level of knowledge about dietary fibre and that, although they give great importance to the role of fibres in treatment and prevention of diseases, the level of intake is too low.